Maestri di strada (Rivista di Studi e Ricerche sulla criminalità organizzata, 2018)
There is growing alarm for criminal recruitment of youths. Education can contribute in thwarting this phenomenon if it manages, through dialogue and reason, to reach the suffering side of youths' spirit: the side where rancor, hatred and fear cumulate. Since reason alone can't penetrate this part of the psyche, a joint effort with art and beauty is necessary to open the mind to the representation of a benevolent world and of a loving care, giving back to youths the meaning of the future. The real challenge in the education of future generations lies in representations and narratives: if the adult world can't present to youths a version of itself where there is space for them, then they will scatter and flock toward the lumps of hatred and fear they find at the margins of suburbs and of the psyche. Those very lumps are the founding cores of the criminal epic narrative helping organized crime to maintain the psychic compliance that is the basis of their recruitment system. “Maestri di Strada”, in the neglected and decaying suburbs of a large city, is trying to create an educating community able to provide youths with experiences in solidarity and sharing that loosen up the bindings of fear and hatred, opening up the possibility of being empowered toward realizing dreams and aspirations rather than submitting to the predetermined scripts of the criminal world. Keywords: education, young, suburbs, narration, social policy